A Critical Realist Theory of Money and Finance: Social Cognitive Semiotics as Metatheory - Oakley, Todd (Recherches sémiotiques / Semiotic Inquiry, 2021)
A nagging question for cognitive semiotics is, “What is the relationship between social structure and agency?” Answers to that question are as elusive as they are essential for explaining the social cognitive facets of meaningful interactions. Elusive in the sense that the social sciences have traditionally lacked ontological rigor in the investigation of social structures and their relationship to individuals. Indeed, the very idea of a social structure is a hotly contested ground. Critical in the sense that many participants within the cognitive semiotics programme aim to explain meaning-making as an emergent property of coordinated activities within normative institutions and organizations. This article aims to provide some measure of ontological rigor to social cognitive semiotics from a critical realist perspective as it applies to the semiotics of money and finance.